Optimization of blending operation for Aswan phosphate mines using linear programming - Ali, Mahrous A.M.; Wasly, H.S.; Abdellah, W.R.; Jang, Hyongdoo (National Mining University, 2018)
Purpose. The economic value of phosphate is reduced when randomly blending raw phosphate produced from different mines. Therefore, the blending process of different raw phosphate ores to produce economic percentage of P2O5 is essential to maximize the profit of a mine as regards suitable mine design. Methods. This paper presents an application of Linear programming (LP) method to determine the optimum quantities of phosphate ore needed per each mine for blending process. Three phosphate operations, located in Aswan pro-vince south of Egypt, have been chosen for this study namely B1, B2 and C. Findings. The results of LP methods reveal that the phosphate ore of 24% of P2O5 will be produced by blending 16.8% of phosphate ore from operation B1, 9.42% of phosphate ore from operation B2 and 73.78% of phosphate ore from operation C. Whilst the phosphate ore of 22% P2O5 will only be obtained by blending 66.43% of phosphate ore from operation B1 and 33.57% from mine B2. Originality. Estimating the suitable height of benches according to stability, safety of work place and efficiency of work place. The suitable height of benches was found according to the efficiency of work place ranged from 12 m to 30 m. Sub benches were divided to keep the assays of the phosphate ores from dilution and the result is that the height of sub bench for overburden ranged from 7 m to 11 m, for the third layer from 0.2 m to 0.3 m, for the upper layer from 0.4 m to 0.6 m and for the lower layer from 0.3 m to 1 m. Practical implications. Applied linear programming in mining as regard mining operations to obtain the optimum solution in mining sites.

Мета. Оптимізація операції змішування фосфатних руд, що добуваються з трьох різних рудників родовища фосфатів (провінція Асуан), на основі використання лінійного програмування для максимізації прибутку гірничого підприємства. Методика. У роботі використано метод лінійного програмування (ЛП) для визначення оптимальної кількості фосфатної руди в процесі змішування, видобутої рудниками на різних ділянках родовища. Для цього розглянуто три фосфатних рудника в провінції Асуан на півдні Єгипту – B1, B2 і C. Для експерименту відібрано три зразки фосфатної руди з кожного рудника, які стадійно перемішувались згідно розробленої схеми. Хімічний склад фосфатних порід, що добуваються з трьох ділянок родовища, визначався спектрофотометричним аналізом. Результати. В процесі лінійного програмування складена цільова функція з урахуванням відпускної ціни та кількості фосфатних руд певного вмісту P2O5, що максимізує прибуток. Виявлено, що у результаті застосування лінійного програмування фосфатна руда із 24% вмістом P2O5 виходить при змішуванні 16.8% руди з рудника B1, 9.42% руди – з рудника B2 та 73.78% руди – з рудника С, а з 22% вмістом – при змішуванні 66.43% руди з рудника B1 і 33.57% руди з рудника B2. Встановлено, що економічна цінність фосфату зменшується при випадковому змішуванні сирих фосфатів, видобутих на різних рудниках. Наукова новизна. Вперше для умов фосфатних рудників Ель-Гера (провінція Асуан) застосовано метод лінійного програмування для оптимізації якості фосфатної руди, що дозволило максимізувати прибуток гірничого підприємства. Практична значимість. Прикладне використання лінійного програмування в гірничій справі дозволяє поліпшити якість видобутої фосфатної руди з різних ділянок родовища провінції Асуан та підвищити її конкурентоспроможність на світовому ринку.

Цель. Оптимизация операции смешивания фосфатных руд, добываемых из трех разных рудников месторождения фосфатов (провинция Асуан), на основе использования линейного программирования для максимизации прибыли горного предприятия. Методика. В работе использован метод линейного программирования (ЛП) для определения оптимального количества фосфатной руды в процессе перемешивания, добытой рудниками на разных участках месторождения. Для этого рассмотрены три фосфатных рудника в провинции Асуан на юге Египта – B1, B2 и C. Для эксперимента отобраны по три образца фосфатной руды из каждого рудника, которые стадийно перемешивались согласно разработанной схемы. Химический состав фосфатных пород, добываемых из трех участков месторождения, определялся спектрофотометрическим анализом. Результаты. В процессе линейного программирования составлена целевая функция с учетом отпускной цены и количества фосфатных руд определенного содержания P2O5, максимизирующая прибыль. Выявлено, что в результате применения линейного программирования фосфатная руда с 24% содержанием P2O5 получается при смешивании 16.8% руды из рудника B1, 9.42% руды – из рудника B2 и 73.78% руды – из рудника С, а с 22% содержанием – при смешивании 66.43% руды из рудника B1 и 33.57% руды из рудника B2. Установлено, что экономическая ценность фосфата уменьшается при случайном смешивании сырых фосфатов, произведенных на разных рудниках. Научная новизна. Впервые для условий фосфатных рудников Эль-Гера (провинция Асуан) применен метод линейного программирования для оптимизации качества фосфатной руды, что позволило максимизировать прибыль горного предприятия. Практическая значимость. Прикладное использование линейного программирования в горном деле позволяет улучшить качество добытой фосфатной руды из разных участков месторождения провинции Асуан и повысить ее конкурентоспособность на мировом рынке.
Keywords: linear programming; blending operation; profit optimization; phosphate ore deposit